UJI AKTIVITAS ANTIKOLESTEROL EKSTRAK BATANG Uncaria cordata (Lour.) Merr. TERHADAP KADAR KOLESTEROL TOTAL MENCIT JANTAN (Mus musculus) - Rika Indriyani; Dewi Handayani; Nurhamidah Nurhamidah; Agus Sundaryono (ALOTROP, 2023)
The aim of this study was to determine the anticholesterol activity of the stem extract of Uncaria cordata (Lour.) Merr. on total cholesterol levels in male mice (Mus musculus). Before carrying out the anticholesterol activity test, phytochemical tests were carried out to determine the content of secondary metabolites in Uncaria cordata stems. Furthermore, the anticholesterol activity test was carried out in vivo using male mice, male mice were induced by high-fat diet (PTL) in the form of beef brain, quail egg yolk and propylthiouracil to increase cholesterol levels in mice until they experienced hypercholesterolemia, then mice were induced by plant extracts to see anticholesterol activity. Cholesterol levels were measured using a glucometer (Autocheck). Phytochemical test results showed the content of secondary metabolites in the form of flavonoids, saponins, alkaloids, tannins and terpenoids. The results of the anti-cholesterol activity test showed that there was anti-cholesterol activity as indicated by a decrease in cholesterol levels in mice with hypercholesterolemia. A decrease of 11.45% at a dose of 5.3 mg/30grW; 12.89% at a dose of 10.2mg/30grW and 21.05% at a dose of 21.2mg/30grW. Key words : Anticholesterol, Uncaria cordata (Lour.) Merr., Hypercholesterolemia